[Over rough seas ; Flower country [videorecording] - Lazaro, Cheche (The Probe Team, 1992)
Probe takes a look at the plight of Filipino fishermen recruited by Eastern Houzon Maritime Sciences, Inc. to work in Taiwan; and Holland famous for its flower industry.